Determination of apoptotic inductive activities of physagulin P from Physalis angulata plant in Vietnam - Yen, Pham Thi Hai; Nga, Nguyen Thi; Phuong, Trieu Ha; Cuc, Nguyen Thi; Phuong, Do Thi; Anh, Hoang Le Tuan; Thi Thao, Do (Vietnam Journal of Biotechnology, 2022)
Currently, multimode treatment is current therapy for cancer that causes various unwanted side effects and costliness for patients. Therefore, finding new natural ingredients derived from plants of which are less toxic and more targeted, are considered to be urgent for development of potential effective drugs to treat cancer due to safety and economic concerns. Physagulin P (VPA22) was known as a novel structural compound, isolated from the species Physalis angulata of the genus Physalis in Vietnam. This active substance has demonstrated cytotoxic effect on lung cancer cell line (A549) with the IC50 value = 13.47±2.73 µM. In our study, VPA 22 was investigated for apoptotic inducing activity on A549 cells by using Hoechst staining, flowcytometry analysis and caspase-3 colorimetric assay. VPA 22 treatment changed the morphology of A549 tending to apoptotic cells whose percentage ranged from 10.09% to 19.18% at the concentration of 5 µM and 15 µM, respectively. In addition, the active ingredient at concentration of 5 µM to 15 µM also significantly activated caspase-3 in turn from 1.30 folds to 2.59 folds. These results together indicated that VPA 22 activated the caspase pathway to trigger out apoptosis on A549 cells and subsequently resulted in inhibition of cancer cell proliferation.